Strategy of Development of Sustainable Red Chili Agribusiness Areas in North Sumatra Province - Novita, Desi; Supriana, Tavi; ., Sirozujilam; Lubis, Satia Negara (Journal of Ecohumanism, 2024)
The development of sustainable red chili agribusiness areas in North Sumatra Province is a challenge that involves various aspects, including cultivation technology, farmer institutions, supply chain efficiency, government policy support, and environmental sustainability. This study aims to identify and formulate a sustainable red chili agribusiness development strategy that can increase farmers' productivity and welfare without sacrificing the environment. Through a qualitative approach, data were collected from in-depth interviews with farmers, agribusiness stakeholders, as well as a review of government policies related to sustainable agriculture. The results show that the application of precision agriculture technology, such as drip irrigation systems and integrated pest management, can significantly increase productivity while preserving natural resources. Strengthening farmer institutions, such as cooperatives, is also very important in coordinating production, improving market access, and stabilizing farmers' income. In addition, supply chain efficiency through the construction of storage and distribution centers will reduce post-harvest losses and price fluctuations, while government policy support is needed in the provision of agricultural infrastructure and stable price regulation. In conclusion, the sustainable development model of red chili agribusiness areas must include synergies between environmentally friendly technologies, strong institutions, efficient supply chains, and proactive policy support. With this model, red chili agribusiness areas in North Sumatra can develop sustainably, contribute to food security, and improve farmers' welfare.